2022
DOI: 10.1186/s41232-022-00210-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in idiopathic pulmonary fibrosis: pathogenesis and therapeutics

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease that occurs due to increased fibrosis of lung tissue in response to chronic injury of the epithelium. Therapeutic options for IPF remain limited as current therapies only function to decrease disease progression. Recently, extracellular vesicles (EVs), including exosomes and microvesicles, have been recognized as paracrine communicators through the component cargo. The population of cell-specific microRNAs and proteins present in EVs can regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Studies have shown that exosomes can alleviate and resolve bleomycin‐induced fibrosis by reconstructing normal alveolar structure, reducing collagen accumulation and decreasing apoptosis. The mechanism may be that MSC‐Exos regulate the phenotype of monocytes to relieve pulmonary fibrosis 27 . Not coincidentally, Xu et al injected human umbilical MSC‐Exos into mice treated with intratracheal silica suspension and found a significant reduction in lung injury and improvement in lung inflammation and fibrosis due to a mechanism, by which umbilical MSC‐Exos reduced collagen deposition in mouse embryonic fibroblasts exposed to SiO 2 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exosomes can alleviate and resolve bleomycin‐induced fibrosis by reconstructing normal alveolar structure, reducing collagen accumulation and decreasing apoptosis. The mechanism may be that MSC‐Exos regulate the phenotype of monocytes to relieve pulmonary fibrosis 27 . Not coincidentally, Xu et al injected human umbilical MSC‐Exos into mice treated with intratracheal silica suspension and found a significant reduction in lung injury and improvement in lung inflammation and fibrosis due to a mechanism, by which umbilical MSC‐Exos reduced collagen deposition in mouse embryonic fibroblasts exposed to SiO 2 28 .…”
Section: Discussionmentioning
confidence: 99%
“…While idiopathic pulmonary fibrosis (IPF) and fibroproliferative ARDS are distinct entities, the underlying pathobiology of these diseases almost certainly share similarities. 6 Extracellular matrix (ECM) abnormally deposits in multi-focus of the lung tissue, accompanied by epithelial and endothelial cell injury, alveolar structure and lung compliance damage, ultimately leading to respiratory failure and death in the pathological process of pulmonary fibrosis. 7 Same as ARDS, therapeutic options for pulmonary fibrosis are also limited as current therapies could only delay disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, therapeutic methods remain limited, as current treatment strategies can only delay the progression of the disease. While idiopathic pulmonary fibrosis (IPF) and fibroproliferative ARDS are distinct entities, the underlying pathobiology of these diseases almost certainly share similarities 6 . Extracellular matrix (ECM) abnormally deposits in multi‐focus of the lung tissue, accompanied by epithelial and endothelial cell injury, alveolar structure and lung compliance damage, ultimately leading to respiratory failure and death in the pathological process of pulmonary fibrosis 7 …”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are lipid bilayer structures secreted by living cells and are classified into either exosomes, microvesicles (MVs), or apoptotic bodies, based on the intracellular production mechanism and size ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , …”
Section: Introductionmentioning
confidence: 99%